2014
DOI: 10.1021/jp5080779
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated Graphene Oxide Platelets in Nafion Nanocomposite Membrane: Advantages for Application in Direct Methanol Fuel Cells

Abstract: Graphene oxide (GO) is well known as an excellent amphiphilic material due to its oxygen-containing functional groups and its chemical tunability. By intercalation chemistry, organo-modified GO containing sulfonilic terminal groups were prepared and used as nanoadditive in Nafion polymer for the creation of hybrid exfoliated composites. The incorporation of hydrophilic 2D platelike layers in the Nafion membranes is expected to induce advantages in terms of thermal stability and mechanical and barrier propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…The proton signal is very wide, about 1 kHz, typical of solid-like configuration, due to the strong confinement of the water molecules within the hydrophilic pores. Clearly, this NMR peak is the convolution of "different" water signals (free and bound to the various hydrophilic groups) in fast rate of proton exchange [7,30]. By increasing temperature, the intensity of this peak decreases because of the water evaporation from the membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The proton signal is very wide, about 1 kHz, typical of solid-like configuration, due to the strong confinement of the water molecules within the hydrophilic pores. Clearly, this NMR peak is the convolution of "different" water signals (free and bound to the various hydrophilic groups) in fast rate of proton exchange [7,30]. By increasing temperature, the intensity of this peak decreases because of the water evaporation from the membranes.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, it may cause some losses in proton conductivity. Although the protons released from the −OH and −COOH groups on the edge of GO nanosheets may contribute to the increment in the proton conductivity of the composite membranes and the acids/hydrophilic sites in GO may retain a certain amount of bound water [30,31]. …”
Section: Characterization Of the Go/nafion Composite Membranesmentioning
confidence: 99%
“…Such structures are more noticeable as the sulfonation level increases because more phase segregation occurs. Other AFM studies also suggest that sGO enchances the morphology , while GO leads to the formation of very homogeneous domains in the membrane . The addition of sGO enhanced the ionic domains and their interconnections, whereas GO incorporation increased the hydrophobic domain of SO 3 H SIBS.…”
Section: Resultsmentioning
confidence: 92%
“…In other similar studies with SPEEK, sGO/S-PEEK nanocomposite membranes presented lower methanol permeability and higher IEC, WU, and proton conductivity than Nafion ® [29,30]. Nicotera and coworkers modified Nafion ® with sGO varying the orientation of the filler in the membranes [31]. Their results suggested that the well-oriented fillers added tortuosity to the membrane producing a reduction in methanol permeation, but in some instances also reducing cell performance.…”
Section: Introductionmentioning
confidence: 94%